Adaptative Mechanisms of Halophytic Eutrema salsugineum Encountering Saline Environment - Li, Chuanshun; Duan, Chonghao; Zhang, Hengyang; Zhao, Yaoyao; Meng, Zhe; Zhao, Yanxiu; Zhang, Quan (Frontiers in Plant Science, 2022)
Salt cress (Eutrema salsugineum), an Arabidopsis-related halophyte, can naturally adapt to various harsh climates and soil conditions; thus, it is considered a desirable model plant for deciphering mechanisms of salt and other abiotic stresses. Accumulating evidence has revealed that compared with Arabidopsis, salt cress possesses stomata that close more tightly and more succulent leaves during extreme salt stress, a noticeably higher level of proline, inositols, sugars, and organic acids, as well as stress-associated transcripts in unstressed plants, and they are induced rapidly under stress. In this review, we systematically summarize the research on the morphology, physiology, genome, gene expression and regulation, and protein and metabolite profile of salt cress under salt stress. We emphasize the latest advances in research on the genome adaptive evolution encountering saline environments, and epigenetic regulation, and discuss the mechanisms underlying salt tolerance in salt cress. Finally, we discuss the existing questions and opportunities for future research in halophytic Eutrema. Together, the review fosters a better understanding of the mechanism of plant salt tolerance and provides a reference for the research and utilization of Eutrema as a model extremophile in the future. Furthermore, the prospects for salt cress applied to explore the mechanism of salt tolerance provide a theoretical basis to develop new strategies for agricultural biotechnology.